The Effect of Pre-emptive Oral Melatonin versus Placebo on Post-operative Analgesia in Infants after Thoracotomy for Closed Cardiac Surgeries: A Randomized Controlled Study - Saleh, Amany; Hassan, Passaint (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Thoracotomy pain is one of the severest types of pain that should be managed properly, especially in children. Opioids are the most widely prescribed analgesics for post-operative pain, but they can have a number of undesirable side effects. Melatonin could be employed as an adjuvant analgesic therapy during procedural discomfort as it had no known major side effects. STUDY DESIGN: This was a double-blinded, controlled randomized study. METHODS: Fifty patients divided randomly into two equal groups. One hour before surgery, children in M group (n = 25) were given 0.5 mg/kg orally of melatonin 3 mg tablets) and patients in Group P (n = 25) received a placebo (5 ml of water by syringe 5 ml) orally. Post-operative pethidine consumption over the 1st 24 h (mg) was recorded, the intraoperative fentanyl consumption (HR and ABP) at baseline, 1 min after induction, at skin incision, and every 30 min till the end of the surgery were recorded. Neonatal Infant Pain Score (NIPS) at 4 h, 6 h, 8 h, 12 h, 18 h, and 24 h postoperatively was recorded. Other reported data include demographic data, extubation time, days of ICU stay, and complications. RESULTS: Total post-operative pethidine consumption (mg) over 24 h was significantly lower in M group than P group (3.48 ± 2.23 vs. 7.68 ± 4.52 p = 0.01). Intraoperative fentanyl consumption (ug) was significantly lower in M group than P group (10.28 ± 4.98 vs. 17.08 ± 7.39 p < 0.001). As regards NIPS, it was statistically lower in M group than P group in all times except at 8 h and 24 h with significant difference. CONCLUSION: Oral melatonin is an effective and safe pre-emptive drug as it reduces the total post-operative pethidine consumption over the first 24 h and decreased post-operative pain scores without any unpleasant effects in pediatrics undergoing closed heart surgery.